Expression optimization of a human papillomavirus type 16 therapeutic vaccine candidate in Nicotiana benthamiana leaves - Do Rosario Yanez, Romana de Jesus (Department of Molecular and Cell Biology, 2017)
High risk human papillomaviruses (HPVs) are the causative agents of cervical cancer. The three approved prophylactic vaccines do not benefit already infected individuals; therefore, there is still an urgent need for therapeutic vaccines. The HPV oncoproteins E6 and E7 are ideal targets for the development of such vaccines, as they are expressed throughout the viral life cycle and in tumours. They could be used to elicit strong cytotoxic lymphocyte (CTL) responses which would aid in viral clearance, and could also be effective against tumours. Granadillo et al. (2011) developed an Escherichia coli-produced therapeutic vaccine candidate, consisting of the HPV-16 E7 protein and a cell membrane- penetrating and immunomodulatory peptide (LALF), whose fusion to HPV-16 E7 aided in the immunogenicity and antigen presentation of the oncoprotein. However, such vaccines need not only to be effective, but also to have a low cost. Plant expression systems represent an attractive alternative to conventional expression systems based on bacterial, yeast, mammalian and other cell cultures, and are potentially far more cost- effective. The aim of the present project was to produce LALF-E7 in Nicotiana benthamiana leaves via Agrobacterium-mediated transient expression, and to optimize its expression, extraction and purification. This was done by expressing LALF-E7 using different expression vectors, testing different subcellular localizations, and testing the effect of gene silencing suppressors. By using our group's replicating expression vector and targeting LALF-E7 to the chloroplasts, the expression of the candidate vaccine in N. benthamiana leaves was increased 26.8 fold compared to non-replicating vectors or cytoplasmic localization. Furthermore, silencing suppressors did not significantly increase the expression of LALF-E7 when expressed by the replicating vector and targeted to the chloroplasts. I showed, by fluorescence microscopy, that LALE-E7 was indeed being targeted to the plants' chloroplasts and that it possibly forms proteins bodies (PBs) that are closely associated to the chloroplast envelope. I further hypothesized a mechanism by which the PBs-like structures form. Once the expression of LALF-E7 was optimized in plant leaves, a purification strategy was developed by testing different extraction methods and using metal ion affinity chromatography. The extraction protocol developed pre-purified LALF-E7 by removing the majority of soluble proteins from the final extract. However, LALF-E7 was not fully purified by affinity chromatography, suggesting that other purification strategies should be used. Finally, I tested the partially purified plant-produced LALF-E7 candidate, and compared it to the E. coli-produced counterpart, in tumour regression experiments using mice as animal models. Due to low antigen doses and a large number tumourigenic cells used to inoculate the mice animal models, the effect of the plant-produced LALF-E7 as a therapeutic vaccine was inconclusive. However, it was suggested that it could potentially be comparable to the E. coli-produced counterpart. In summary, I report for the first time the entire chain of research involving the expression of LALF-E7 in plants, its extraction, purification and the testing of its immunogenicity in a mouse model. This research also suggests new avenues for the use of the LALF peptide as a PB-inducer which could be useful in increasing the expression of other recombinant proteins.